Impacto do uso da água de cisternas na ocorrência de episódios diarréicos na população rural do agreste central de Pernambuco, Brasil The impact of the use of water from water-tanks on the occurrence of diarrhea in the rural population of the Central Agreste region of the Brazilian State of Pernambuco - Carlos Feitosa Luna; Ana Maria de Brito; André Monteiro Costa; Tiago Maria Lapa; James A Flint; Pasha Marcynuk (Instituto Materno Infantil de Pernambuco, 2011)
OBJETIVOS: avaliar o impacto do uso da água de cisternas na ocorrência de episódios diarréicos comparando o número e a duração de episódios entre moradores de domicílios com e sem cisternas, numa mesma área geográfica. MÉTODOS: estudo longitudinal prospectivo aninhado a um estudo de corte transversal com dois grupos de comparação (domicílios com e sem cisternas) realizado, em 21 municípios do Agreste Central de Pernambuco, em 2007. O período de coleta foi de 60 dias, e incluiu 1765 indivíduos. Para análise descritiva utilizou-se modelos mistos hierárquicos, Mann-Whitney e Kaplan-Meyer com nível de significância de 5%. RESULTADOS: entre os 949 indivíduos com cisternas, obteve-se uma redução no risco de ocorrência de episódios diarréicos de 73% quando comparados aos 816 indivíduos sem cisternas (RR=0,27; p<0.001). O número médio de episódios registrados nos residentes de domicílios sem cisternas foi de 0,48 (DP=1,17), contra 0,08 (DP=0,32) nos domicílios com cisternas(z=-10,26; p<0,001). A duração média dos episódios foi 1,5 vezes maior nos domicílios sem cisternas (χ²=8,99; p=0,003). CONCLUSÕES: os achados deste estudo destacam a importância do acesso à água potável na redução de doenças. A ocorrência de diarréia, bem como, seus indicadores de gravidade - número de episódios e duração da diarréia foram consistentemente maiores nos residentes de domicílios sem cisternas. OBJECTIVES: to evaluate the impact of the use of water-tanks on the occurrence of episodes of diarrhea, comparing the number and duration of episodes among the residents of households with and without water-tanks in the same geographical area. METHODS: a longitudinal prospective study, nested in a cross-section study comparing two groups (households with and without water-tanks), was carried out in 21 municipalities in the Central Agreste region of the Brazilian State of Pernambuco, in 2007. Data was gathered over 60 days and included 1,765 individuals. Descriptive analysis was carried out using mixed hierarchical models, Mann-Whitney and Kaplan-Meyer with the level of significance set at 5%. RESULTS: among the 949 individuals with water-tanks, there was a reduction in the risk of the occurrence of episodes of diarrhea of 73% compared with the 816 individuals without water-tanks (RR=0.27; p<0.001). The mean number of episodes registered among residents of households without water-tanks was 0.48 (SC=1.17), compared with 0.08 (SC=0.32) among households with water-tanks (z=-10.26; p<0.001). The mean during of episodes was 1.5 times greater in households without water-tanks (χ2=8.99; p=0.003). CONCLUSIONS: the findings of this study point to the importance of access to drinking water for the reduction of disease. The occurrence of diarrhea and its concomitant severity indicators-number of episodes and duration-were consistently higher among residents of households without water-tanks.